Comprehensive Review on Thermoelectric Electrodeposits: Enhancing Thermoelectric Performance Through Nanoengineering - Wu, Tingjun; Kim, Jiwon; Lim, Jae-Hong; Kim, Min-Seok; Myung, Nosang V. (Frontiers in Chemistry, 2021)
Thermoelectric devices based power generation and cooling systemsystem have lot of advantages over conventional refrigerator and power generators, becausebecause of solid-state devicesdevices, compact size, good scalability, nono-emissions and low maintenance requirement with long operating lifetime. However, the applications of thermoelectric devices have been limited owingowing to their low energy conversion efficiency. It has drawn tremendous attention in the field of thermoelectric materials and devices in the 21st century because of the need of sustainable energy harvesting technology and the ability to develop higher performance thermoelectric materials through nanoscale science and defect engineering. Among various fabrication methods, electrodeposition is one of the most promising synthesis methods to fabricate devices because of its ability to control morphology, composition, crystallinity, and crystal structure of materials through controlling electrodeposition parameters. Additionally, it is an additive manufacturing technique with minimum waste materials that operates at near room temperature. Furthermore, its growth rate is significantly higher (i.e., a few hundred microns per hour) than the vacuum processes, which allows device fabrication in cost effective matter. In this paper, the latest development of various electrodeposited thermoelectric materials (i.e., Te, PbTe, Bi2Te3 and their derivatives, BiSe, BiS, Sb2Te3) in different forms including thin films, nanowires, and nanocomposites were comprehensively reviewed. Additionally, their thermoelectric properties are correlated to the composition, morphology, and crystal structure.